Changes of oxygen isotope values of soil P pools associated with changes in soil pH - Pfahler, Verena; Macdonald, Andy; Mead, Andrew; Smith, Andrew C.; Tamburini, Federica; Blackwell, Martin S. A.; Granger, Steven J. (Scientific reports, 2020)
Field data about the effect of soil pH on phosphorus (P) cycling is limited. A promising tool to study P cycling under field conditions is the 18 O: 16 O ratio of phosphate (δ 18 O P ). In this study we investigate whether the δ 18 O P can be used to elucidate the effect of soil pH on P cycling in grasslands. Soils and plants were sampled from different fertilisation and lime treatments of the Park Grass long term experiment at Rothamsted Research, UK. The soils were sequentially extracted to isolate different soil P pools, including available P and corresponding δ 18 O P values were determined. We did not observe changes in plant δ 18 O P value, but soil P δ 18 O P values changed, and lower δ 18 O P values were associated with higher soil pH values. At sites where P was not limiting, available P δ 18 O P increased by up to 3‰ when lime was applied. We show that the δ 18 O P method is a useful tool to investigate the effect of pH on soil P cycling under field conditions as it highlights that different soil processes must govern P availability as pH shifts. The next challenge is now to identify these underlying processes, enabling better management of soil P at different pH.